2023
DOI: 10.1099/jmm.0.001731
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-sensitive Enterococcus faecium bacteraemia – hospital transmission and mortality in a Danish University Hospital

Abstract: Introduction. The emergence of vancomycin-resistant Enterococcus faecium (VREfm) has left the vancomycin-sensitive E. faecium (VSEfm) strains almost unnoticed. Hypothesis. Molecular characteristics, hospital transmission patterns and clinical impact of VSEfm have changed, and VSEfm is a predictor of VREf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“… 20 , 62 , 75 , 76 However, recent analysis from a single hospital in Denmark found no genomic relatedness between VSEfm and VREfm clones over a 4 year period suggesting vancomycin resistance acquisition by VSEfm is not always frequent and these may represent different transmission networks. 77 Also, we relied on direct plating to solid VREfm screening agar for inclusion in our study. Previous studies have shown a sensitivity of 58%–96% for this approach, rising to 97%–100% with a pre-enrichment step.…”
Section: Resultsmentioning
confidence: 99%
“… 20 , 62 , 75 , 76 However, recent analysis from a single hospital in Denmark found no genomic relatedness between VSEfm and VREfm clones over a 4 year period suggesting vancomycin resistance acquisition by VSEfm is not always frequent and these may represent different transmission networks. 77 Also, we relied on direct plating to solid VREfm screening agar for inclusion in our study. Previous studies have shown a sensitivity of 58%–96% for this approach, rising to 97%–100% with a pre-enrichment step.…”
Section: Resultsmentioning
confidence: 99%